A district-level susceptibility and vulnerability assessment of the COVID-19 pandemic's footprint in India. (February 2021) - Imdad, Kashif; Sahana, Mehebub; Rana, Md Juel; Haque, Ismail; Patel, Priyank Pravin; Pramanik, Malay
Highlights: Examines the spread of the COVID-19 pandemic in India in four separate time steps. Uses geospatial and geostatistical measure to identify viral hotspots and clusters. Analyses COVID-19′s correlates at the district level, eliciting detailed outputs. Gauges epidemiological susceptibility and socioeconomic vulnerability to COVID-19. Provides a framework for denoting districts where lockdown measures can be eased. Abstract: In this study, we trace the COVID-19 pandemic's footprint across India's districts. We identify its primary epicentres and the outbreak's imprint in India's hinterlands in four separate time-steps, signifying the different lockdown stages. We also identify hotspots and predict areas where the pandemic may spread next. Significant clusters in the country's western and northern parts pose risk, along with the threat of rising numbers in the east. We also perform epidemiological and socioeconomic susceptibility and vulnerability analyses, identifying resident populations that may be physiologically weaker, leading to a high incidence of cases and pinpoint regions that may report high fatalities due to ambient poor demographic and health-related factors. Districts with a high share of urban population and high population density face elevated COVID-19 risks. Aspirational districts have a higher magnitude of transmission and fatality. Discerning such locations can allow targeted resource allocation to combat the pandemic's next phase in India.